A 2 ?m, gain-switched Tm-doped fiber laser and amplifier system with output average power of 9 W at 50 kHz - Swiderski, Jacek; Michalska, Maria; Pichola, Wieslaw; Kwiatkowski, Jacek; Galecki, Lukasz (Photonics Letters of Poland, 2013)
We demonstrate a gain-switched thulium-doped fiber laser and amplifier system (TDFL&A) operating at a wavelength of 1994.7 nm. A pulsed fiber Master Oscillator Power Amplifier (MOPA) at 1.55 ?m was used to gain-switch the Tm fiber laser via in-band pumping. In the next step, the gain-switched pulses were amplified in a cladding-pumped Tm-doped fiber amplifier pumped by up to 30 W at 793 nm. For the pulse repetition frequency (PRF) of 100 kHz, the laser system delivered the maximum average output power as high as 9.03 W with a slope efficiency of 36.4%. For the PRF of 50 kHz, stable 25-ns pulses with energy of 0.18 mJ corresponding to a peak-power of 6.8 kW were achieved. The performance of the laser system is described. Full Text: PDF References N. J. Scott, C. M. Cilip, N. M. Fried, "Thulium Fiber Laser Ablation of Urinary Stones Through Small-Core Optical Fibers", IEEE J. Sel. Top. Quantum Electron. 15, 435 (2009). CrossRef M. Baudelet, C. C. C. Willis, L. Shah, M. Richardson, "Laser-induced breakdown spectroscopy of copper with a 2 ?m thulium fiber laser", Opt. Express 18, 7905 (2010). CrossRef G. J. Koch, J. Y Beyon, B. W. Barnes, M. Petros, J. Yu, F. Amzajerdian, M. J. Kavaya, U. N. Singh, "Novel nonlinear adaptive Doppler-shift estimation technique for the coherent Doppler validation lidar", Opt. Eng. 46, 116201 (2007). CrossRef P. Sprangle, A. Ting, J. Penano, R. Fischer, B. Hafizi, "Incoherent Combining and Atmospheric Propagation of High-Power Fiber Lasers for Directed-Energy Applications", IEEE J. Quantum Electron. 45, 138 (2009). CrossRef D. Creeden et al., "Mid-infrared ZnGeP2 parametric oscillator directly pumped by a pulsed 2??m Tm-doped fiber laser", Opt. Lett. 33, 315 (2008). CrossRef J. Swiderski, M. Michalska, "Mid-infrared supercontinuum generation in a single-mode thulium-doped fiber amplifier", Laser Phys. Lett. 10, 035105 (2013). CrossRef A. S. Kurkov et al., "Supercontinuum generation in thulium-doped fibres", Quantum Electron. 42, 778 (2012). CrossRef T. Ehrenreich, R. Leveille, I. Majid, K. Tankala, "1-kW, all-glass Tm:Fiber laser," in Proc. Fiber Laser VII: Technol. Syst. Applicat., 1-15 (2010). M. Eckerle, C. Kieleck, J. Swiderski, S. D. Jackson, G. Maze, M. Eichhorn, "Actively Q-switched and mode-locked Tm3+-doped silicate 2?m fiber laser for supercontinuum generation in fluoride fiber" Opt. Lett. 37, 512-514 (2012). CrossRef F. Stutzki, F. Jansen, C. Jauregui, J. Limpert, A. Tunnermann, "2.4 mJ, 33 W Q-switched Tm-doped fiber laser with near diffraction-limited beam quality", Opt. Lett. 38, 97 (2013). CrossRef G. Sobon, J. Sotor, I. Pasternak, A. Krajewska, W. Strupinski, K. M. Abramski, "Thulium-doped all-fiber laser mode-locked by CVD-graphene/PMMA saturable absorber", Opt. Express 21, 12797 (2013). CrossRef N. Simakov, A. Hemming, S. Bennetts, J. Haub, "Efficient, polarised, gain-switched operation of a Tm-doped fibre laser", Opt. Express 19, 14949 (2011). CrossRef M. Eichhorn, "Development of a high-pulse-energy Q-switched Tm-doped double-clad fluoride fiber laser and its application to the pumping of mid-IR lasers", Opt. Lett. 32, 1056 (2007). CrossRef A. F. El-Sherif, T. King, "High-peak-power operation of a Q-switched Tm3+-doped silica fiber laser operating near 2 ?m", Opt. Lett. 28, 22 (2003). CrossRef J. Swiderski, A. Zajac, P. Konieczny, M. Skorczakowski, "Numerical model of a Q-switched double-clad fiber laser", Opt. Express 12, 3554 (2004). CrossRef Y. Tang, F. Li, J. Xu, "High Peak-Power Gain-Switched Tm ^{3+} -Doped Fiber Laser", IEEE Phot. Tech. Lett. 23, 893 (2011). CrossRef M. Jiang, P. Tayebati, "Stable 10ns , kilowatt peak-power pulse generation from a gain-switched Tm-doped fiber laser", Opt. Lett. 32, 1797 (2007). CrossRef J. Swiderski, M. Maciejewska, J. Kwiatkowski, M. Mamajek, "An all-fiber, resonantly pumped, gain-switched, 2 ?m Tm-doped silica fiber laser", Laser Phys. Lett. 10, 015107 (2013). CrossRef Y. Tang, L. Xu, Y. Yang, J. Xu, "High-power gain-switched Tm3+-doped fiber laser", Opt. Express 18, 22964 (2010). CrossRef